(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
In under developed countries some local people traditionally use herbs to boost milk production or induction of lactation than the antipsychotic drugs that have serious side effects like drowsiness and depression. The objective of this study was to determine molecular pathway for mRNA gene expression of Oxytocin receptor (OTR) in lactogenic effect of Hibiscus sabdariffa L. Fifteen lactating Wistar rats grouped into five (n=5), control group received 1 ml/kg of distilled water, metoclopramide group received 5 mg/kg and ethyl acetate fraction of Hibiscus sabdariffa L group received 800 mg/kg for 14 days. Serum, milk production, milk yield, mammary gland and pup weight (daily) were collected for analysis. Results showed that the ethyl acetate fraction of Hibiscus sabdariffa L. increased significantly (p<.05) daily milk yield [(0.72ml) (0.52ml)] and pup weight [(3.3ml) (2.5ml)] compared to the control group. It also increased the level of oxytocin [(19.26±1.3ng/mL) (10.18±1.5ng/mL)], oestradiol [(565.4±28ng/mL) (562.3±38ng/mL)], progesterone [(64.5±19ng/mL) (46.3±12ng/mL)], Thyroxine (T3 & T4) [(1.54±0.1ng/mL) (1.02±0.1ng/mL)] [(73.2±2.8ng/mL) (55.6±2.2ng/mL)] and growth hormone [(54.6±2.1ng/mL) (29.0±1.7ng/mL)] significantly (p<.05). Mammary gland of ethyl acetate fraction of Hibiscus sabdariffa L. group showed clear lobuloalveolar development and proliferation of myoepithelial cells, with striking variations observed among the groups. The ethyl acetate fraction of Hibiscus sabdariffa L. down regulate the mRNA expression of OTR receptor [(20.42IU/ml) (21.82IU/ml)]. In conclusion, ethyl acetate fraction of Hibiscus sabdariffa L. enhance lactogenic activity through increasing hormonal level, lobuloalveolar development of the mammary gland and down regulates mRNA gene expression of OTR receptor in rats.